Mapping landscapes: integrating GIS and social science methods to model human-nature relationships in southern Cameroon - Robligio, V.; Mala, W.A.; Diaw, C. (2003)
Participatory mapping and GIS are both necessary to model the interactions betwen humans and their environment. A case study from the forest margin in the Congo Basin demonstrates how data from participatory community mapping and other social science methods can be prepared for quantitative modelling. This approach bridged the gap between spatial modelling data and social decision-making in space by elaborating a geographically consistent social representation of the landscape and giving a geographical base to the connection between land use, its cultural representation, and its social management. This was achieved through an iterative process of GIS cartography, using feedback from village informants and field checking, to transpose the spatial references from participatory mapping sketches into reliable geographic locations. As well as demonstrating the utility of such data for modelling, this work clarified the distribution of land rights among the six main owner-clans spread through the eight hamlets in the watershed. The 'basin' of spatial resources and its relation to the rules of land use and natural resource management were defined for each clan. Land-use systems at the forest-agriculture interface in the study area proved to be complex, strongly driven by social rules and influenced by history and settlement strategies. These social and historical aspects established the framework within which communities make current decisions and intervention.